Influence of Work Motivation, Work Environment, and Employee Competence on Employee Performance Through Organizational Commitment as Intervening Variable - Kuswantoro, Agung; Zaidaan, Akmal (Economic Education Analysis Journal, 2023)
Performance is an overview of the results of a program or policy to achieve organizational goals. Based on the initial observations related to the performance of the Gunungpati Sub-district Office employees, many issues were still found. They are to be evaluated and improved. This study examines the influence of work motivation, work environment, and employee competence on employee performance through organizational commitment as an intervening variable. The population and sample in this study were all employees of the Gunungpati Sub-district Office, namely 135 people. This study applied non-probability sampling with a saturated sampling technique. Data analysis methods were descriptive statistical and path analysis using the IBM SPSS Statistic 25. The results point out that four variables, namely work motivation, work environment, employee competence, and organizational commitment, partially have a positive and significant impact on employee performance. Path analysis test shows that three variables, namely work motivation, work environment, and employee competence, have a positive and significant effect on employee performance through organizational commitment as an intervening variable.